2020
DOI: 10.2337/dc19-2331
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Fat and Postprandial Glycemia Increase After Consumption of a Diet Enriched in Saturated Fat Compared With Free Sugars

Abstract: Debate continues regarding the influence of dietary fats and sugars on the risk of developing metabolic diseases, including insulin resistance and nonalcoholic fatty liver disease (NAFLD). We investigated the effect of two eucaloric diets, one enriched with saturated fat (SFA) and the other enriched with free sugars (SUGAR), on intrahepatic triacylglycerol (IHTAG) content, hepatic de novo lipogenesis (DNL), and whole-body postprandial metabolism in overweight males. RESEARCH DESIGN AND METHODSSixteen overweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 44 publications
8
33
0
2
Order By: Relevance
“…In line with this, a very recent study showed that also an isocaloric diet enriched in SFA increased liver fat and postprandial glycaemia, whereas an isocaloric diet high in sugar had no effect on liver fat and induced only minor metabolic changes. [ 18 ]…”
Section: Sfa Lead To the Development Of Liver Steatosis In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, a very recent study showed that also an isocaloric diet enriched in SFA increased liver fat and postprandial glycaemia, whereas an isocaloric diet high in sugar had no effect on liver fat and induced only minor metabolic changes. [ 18 ]…”
Section: Sfa Lead To the Development Of Liver Steatosis In Humansmentioning
confidence: 99%
“…Interestingly, while the present article was under review, a study was published which showed that humans given an isocaloric diet high in SFA also increased their liver fat and postprandial glycaemia, whereas a isocaloric diet high in sugar had no effect on liver fat and induced only minor metabolic changes. [ 18 ] Studies are now needed to compare the effect of an isocaloric diet high in SFA with an isocaloric diet high in PUFA on liver fat, and with a stronger focus toward underlying mechanisms. Of note, studies should also look into the possible differential effects of SFA originating from dairy sources as opposed to SFA coming from meat.…”
Section: Future Directionsmentioning
confidence: 99%
“…Indeed, Hodson's team recently demonstrated that feeding SFAs increased hepatic lipogenesis to a greater extent than simple sugars did. 111 When the data are taken together, the belief that dietary composition plays a significant role in metabolic disease development is supported by strong clinical and experimental data (Figs 1 and 3). Excessive consumption of specific dietary drivers favors metabolic inflammation and insulin resistance, and dietary modulation plays a significant role in risk of T2D and NAFLD.…”
Section: Hyperglycemia Versus Dietary Sugarsmentioning
confidence: 92%
“…Dietary fat uptake is commonly measured by using FA tracers enriched with the stable carbon isotope 13 C [ 7 , 8 , 9 ▪▪ , 10 ▪▪ ] or deuterium ( 2 H) [ 5 , 6 , 11 , 12 ], due to their low natural abundance (1.1 and 0.015%, respectively). Usually, a meal with 13 C-labeled palmitate, deuterated tri-palmitate or [ 2 H 35 ] stearate is given to trace incorporation of meal fat in VLDL triglyceride (VLDL-TG) [ 5 8 , 9 ▪▪ , 10 ▪▪ , 11 , 12 ]. The FA composition and the tracer enrichment were shown to be similar in VLDL-TG and liver triglyceride (determined from liver biopsies), therefore the tracer enrichment of plasma VLDL-TGs can be used as a surrogate for liver fat enrichment and can be used to determine hepatic storage of meal fat [ 5 , 13 ].…”
Section: Techniques Determining Dietary Fat Uptakementioning
confidence: 99%